Evaluasi program pelatihan menjahit di UPTD BLK Kota Palangka Raya dengan menggunakan Model CIPPO - Gustianae, Tity; I Nyoman Sudyana; Indrajaya, Kusnida (Jurnal Praksis dan Dedikasi Sosial, 2025)
Evaluation of the sewing training program at the UPTD BLK in Palangka Raya City using the CIPPO Model The objective of this study is to evaluate the achievement of a training program as an effort to assess its effectiveness at the Regional Technical Implementation Unit of the Vocational Training Center (UPTD BLK) in Palangka Raya City, with a specific focus on the sewing training program. The program evaluation concentrates on five key aspects: context, input, process, product, and outcomes. The theoretical discussion in this study applies a descriptive mixed-methods approach, utilizing the CIPPO evaluation model. The data analysis process includes data collection, data condensation, data display, and conclusion drawing/verifying, with data validation conducted through triangulation and member checking. The overall findings of the program evaluation indicate that the implementation of the vocational training program at UPTD BLK Palangka Raya has been carried out fairly well. Among the five aspects analyzed, the product aspect is of particular concern, as the graduation rate of sewing training participants who achieved BNSP national standard certification has not yet reached 100%. Meanwhile, the outcome evaluation, which measures the effectiveness of the competency-based program, showed a 95% achievement rate, reflecting very strong performance. The main challenge identified involves maximizing the use of available equipment, including sharing the use of overlock (obras) sewing machines, allowing participants to continue practicing throughout the training. Additionally, these issues are reported in the program’s final report to the Palangka Raya City Government. Tujuan daripada penelitian ini guna mengevaluasi pencapaian program pelatihan sebagai upaya dalam menilai efektivitas program tersebut di Unit Pelaksana Teknis Daerah Balai Latihan Kerja Kota Palangka Raya, secara khusus pada bidang pelatihan menjahit. Evaluasi program memfokuskan pada 5 (lima) aspek: context, input, process, product, dan outcomes. Pembahasan teori dalam penelitian mengenai program ini menerapkan metode deskriptif mixed methods, dengan evaluasi model CIPPO. Analisa data meliputi data collection, data condensation, data display, conclusion, drawing/verifying serta dilakukan validasi data melalui triangulasi dan member check. Temuan penelitian evaluasi program secara keseluruhan, hasil evaluasi mengungkapkan bahwa pelaksanaan program pelatihan kerja di UPTD BLK Kota Palangka Raya telah berjalan dengan cukup baik. Di antara lima aspek yang dianalisis, aspek product menjadi perhatian utama, karena tingkat kelulusan peserta pelatihan menjahit dengan sertifikasi standar nasional BNSP belum mencapai 100%. Sementara itu, hasil evaluasi outcome yang mengukur efektivitas program berbasis kompetensi menunjukkan pencapaian 95%, yang mencerminkan kinerja sangat baik. Kendala yang ada yaitu dengan memaksimalkan penggunaan peralatan yang ada, menggunakan mesin obras secara bergantian, sehingga peserta tetap bisa melakukan praktik selama pelatihan, serta menyampaikan permasalahan dalam laporan akhir program kepada Pemda Kota Palangka Raya.